Más allá de la filosofía del lenguaje (pp. 135-150). Trad. de María J. Rebollo y Miguel A. Pastor. - Modica, Giuseppe (Cuadernos sobre Vico, 2020)
CUADERNOS SOBRE VICO, 9-10 (1998). 498 págs. ISBN 1130-7498